2010
DOI: 10.1111/j.1574-6976.2009.00204.x
|View full text |Cite
|
Sign up to set email alerts
|

Indole as an intercellular signal in microbial communities

Abstract: Bacteria can utilize signal molecules to coordinate their behavior to survive in dynamic multispecies communities. Indole is widespread in the natural environment, as a variety of both Gram-positive and Gram-negative bacteria (to date, 85 species) produce large quantities of indole. Although it has been known for over 100 years that many bacteria produce indole, the real biological roles of this molecule are only now beginning to be unveiled. As an intercellular signal molecule, indole controls diverse aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
686
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 802 publications
(702 citation statements)
references
References 170 publications
(290 reference statements)
11
686
1
4
Order By: Relevance
“…In Pseudomonas putida , signalling molecules such as indole enhances TtgGHI efflux pump that are relevant for antibiotic resistance (Molina‐Santiago et al ., 2014). The previous studies have reported that indole inhibits biofilm formation and suppresses the virulence of bacterial strains such as Staphylococcus aureus , Agrobacterium tumefaciens (Lee and Lee, 2010; Lee et al ., 2013, 2015a,b; Lee et al ., 2016) and Vibrio cholera (Mueller et al ., 2009). Likewise, indole derivatives such as 7‐fluoroindole, 7‐hydroxyindole, 3‐indolyl acetonitrile and 2‐aminobenzimidazoles have been reported to exhibit antimicrobial activities against pathogenic bacteria (Lee et al ., 2009, 2011, 2012, 2015a,b; Frei et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Pseudomonas putida , signalling molecules such as indole enhances TtgGHI efflux pump that are relevant for antibiotic resistance (Molina‐Santiago et al ., 2014). The previous studies have reported that indole inhibits biofilm formation and suppresses the virulence of bacterial strains such as Staphylococcus aureus , Agrobacterium tumefaciens (Lee and Lee, 2010; Lee et al ., 2013, 2015a,b; Lee et al ., 2016) and Vibrio cholera (Mueller et al ., 2009). Likewise, indole derivatives such as 7‐fluoroindole, 7‐hydroxyindole, 3‐indolyl acetonitrile and 2‐aminobenzimidazoles have been reported to exhibit antimicrobial activities against pathogenic bacteria (Lee et al ., 2009, 2011, 2012, 2015a,b; Frei et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The auxin acts as an effector molecule between IAA-producing bacteria and plants, and bacteria -bacteria interactions have been discussed in several reviews. 3,4,14,15 However, IAA biosynthetic pathways and the role of IAA in fungal ecology have not been widely investigated. 6,16,17 In this review, we address the aforementioned issues.…”
Section: Introductionmentioning
confidence: 99%
“…Indole is the metabolic product of tryptophan generated by tryptophanase enzymatic activity encoded by tnaA gene in E. coli [1]. It is also produced by bacteria in the rumen and many living systems as a product of tryptophan metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Various industries that synthesize pharmaceuticals, cosmetics, pesticides, disinfectants, agrochemicals, and dyes are also considered sources of indole [2]. There are more than 85 Gram-positive and Gram-negative bacterial species that yield indole as the product of tryptophan metabolism [1]. Biochemical and molecular studies have shown that indole plays various roles in bacterial systems, for example, as an extracellular signal [1,3], for multicopy plasmid maintenance [4], cell division, biofilm formation [5], and acid and drug resistance [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation